(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article examines the impact of the implementation of regional industrial projects on the development of the region’s economy. The authors carried out an analysis of the implementation of projects in the period from 2010 to 2016 in the framework of the state program of industrial and innovative development in the Zhambyl region. In the course of the study, an analysis of the implementation of regional industrial projects in the sectoral context over the past seven years was carried out. Based on the analysis, the impact of the implementation of projects on the diversification of the region’s economy was determined and the impact on improving the socio-economic indicators of the region was examined. In particular, the impact of the implementation of industrial projects on the employment of the population in the region has been studied.